Palatal implants for primary snoring: short-term results of a new minimally invasive surgical technique - Maurer, Joachim T.; Verse, Thomas; Stuck, Boris; Hörmann, Karl; Hein, Gerhard (Otolaryngology - head and neck surgery, 2005)
OBJECTIVE:, To determine the safety and efficacy of a new soft palate implant procedure for the reduction of snoring., STUDY DESIGN AND SETTING:, Fifteen healthy patients with primary snoring due to palatal flutter were enrolled into this prospective study after clinical and endoscopic examination and polysomnography. The average age of the patients was 41.2 ± 8.6 years with a body mass index of 26.2 ± 2.5 kg/m2. The Anti-Snoring Device consists of a delivery tool with a cylindrical implant of braided polyester filaments. Under local anesthesia, three implants intended for permanent implantation were placed into the soft palate. Snoring-related symptoms were assessed by visual analogue scales (VAS), polysomnography, and the SNAP system at baseline and 90 days postoperatively., RESULTS:, All implants were placed without complications. Only minor discomfort was reported in four cases within the first three days postprocedure. At the 90-day follow-up snoring was reduced from 7.3 ± 1.6 to 2.5 ± 2.1 (VAS, P < 0.01) and from 347 ± 239 to 264 ± 168 snoring sounds/hour (SNAP, P > 0.05). Polysomnography did not show any deterioration of sleep or breathing. Speech, swallowing, and taste were unchanged., CONCLUSION:, The Anti-Snoring Device is a new surgical tool offering a simple and minimally invasive procedure. Our data demonstrate that the treatment is safe and effective with good patient acceptance. Further patient follow-ups are needed to evaluate the long-term results.
Gesehen am 18.03.2022